2015
DOI: 10.1101/gr.192518.115
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of alternative splicing in Drosophila by 56 RNA binding proteins

Abstract: Alternative splicing is regulated by RNA binding proteins (RBPs) that recognize pre-mRNA sequence elements and activate or repress adjacent exons. Here, we used RNA interference and RNA-seq to identify splicing events regulated by 56 Drosophila proteins, some previously unknown to regulate splicing. Nearly all proteins affected alternative first exons, suggesting that RBPs play important roles in first exon choice. Half of the splicing events were regulated by multiple proteins, demonstrating extensive combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 59 publications
(78 reference statements)
15
86
0
Order By: Relevance
“…In Drosophila cells, splicing factors act combinatorially to regulate splicing events and more than half of splicing events are regulated by more than one splicing factor (Brooks et al, 2015). Thus, we next asked whether the splicing factors that were necessary for visual function were also required for any of the age‐regulated splicing events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila cells, splicing factors act combinatorially to regulate splicing events and more than half of splicing events are regulated by more than one splicing factor (Brooks et al, 2015). Thus, we next asked whether the splicing factors that were necessary for visual function were also required for any of the age‐regulated splicing events.…”
Section: Resultsmentioning
confidence: 99%
“…The binding of splicing factors to elements within the nascent transcript largely governs the differential inclusion of exons, thereby determining the splicing outcome of a particular transcript (Matera & Wang, 2014). Knockdown of individual splicing factors in cultured Drosophila cells revealed that half of all splicing events are regulated by more than one splicing factor, illustrating the complicated and combinatorial effect of splicing factors in determining splice‐site usage (Brooks et al, 2015). …”
Section: Introductionmentioning
confidence: 98%
“…'GT-AG','GC-AG' and 'AT-AC'. We filtered those junctions that were not included in FlyBase by requiring a Shannon entropy (GRAVELEY et al 2011;BROOKS et al 2015) higher than 2 in both datasets. Altogether, we detected 66,724 junctions (61,056 of which were annotated in Flybase r6.08 and 6,588 were novel).…”
Section: Processing Of Rna-seq Readsmentioning
confidence: 99%
“…To assess potential biological functions of the RNA-protein interactions identified in this study, we compared our RIP-seq results to RNA-seq data generated by Brooks et al (2015) after RNAi knockdown of 14 of the RBPs included in this study (SRP54, CG6227, RM62, MUB, QKR54B, UPF1, B52, RBP1, ELAV, SNRNP70K, SYP, SC35, TRA2, and FMR1). Although the extent of protein depletion was not monitored by Brooks et al (2015) due to the lack of antibodies, depletion of the target mRNAs was confirmed by RT-PCR and analysis of the RNA-seq data (see Supplementary Materials of Brooks et al 2015).…”
Section: Binding Events Identified By Rip-seq Are Functionalmentioning
confidence: 99%